ESTABLISHING COOPERATION THROUGH MULTIMEDIA TOOLS IN MOTHER TONGUE CLASSES (Proximus Journal of Sports Science and Physical Education, 2025)
The article discusses the effective use of multimedia tools in native language lessons, the role and importance of multimedia technologies in various forms of lessons. The opinions of methodologists are analyzed. The issues of establishing a cooperative pedagogy through multimedia tools are covered